Answer: Choice D) 4x^2+18x+18
==============================================
Step-by-step explanation:
Let's add the lengths across the top
(2x+7)+(2x-1)
2x+7+2x-1
(2x+2x)+(7-1)
4x+6
The total horizontal length of the two rooms combined is 4x+6
Multiply this with the vertical length (x+3) getting
(4x+6)(x+3)
y(x+3) .... see note below
y*x + y*3
x(y) + 3(y)
x(4x+6) + 3(4x+6)
4x^2+6x + 12x + 18
4x^2+18x+18
which is the total area of both rooms combined
Note: I replaced (4x+6) with y in step 2 above. That helps with distribution though it's not mandatory. You could also use the FOIL rule or the box method as alternative options.
Another alternative option is to find the area of each individual room and then add up the two smaller areas to get the larger total area.